(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. It is known that rhegmatogenous retinal detachment is complicated in 0.5–4 % cases by ciliochoroidal detachment, hypotension, and uveitis. Definitely, ciliary body dysfunction plays an important role in the pathogenesis of these complications but its morphological changes is not represented in the literature. Existing methods of diagnosis detached ciliary body are imperfect and require further development. Aim to develop an ultrasonic methodology of ciliary body scanning in rhegmatogenous retinal detachment cases complicated by ciliochoroidal detachment. Material and methods. 39 patients with rhegmatogenous retinal detachment complicated by choroidal detachment, conducted eye examination: visual acuity, perimetry, biomicroscopy, ophthalmoscopy, tonometry, ultrasound examination, including ciliary body, choroid and retina. Results. The developed method of ciliary body thickness evaluation in area of its processes allows reducing measurement error with ciliochoroidal and retinal detachment. It was found that all patients had ciliary body detachment spreading to the choroid and accompanied by its edema. Averages thickness in processes zone in four meridians ranged from (0,82 ± 0,01) to (0,84 ± 0,01) mm. Ciliary body edema feature during its detachment is disorganization of the outer layers of the flat part, which is manifested by the presence of a plurality of individual small oblique fibers. Conclusions. The proposed method of ciliary body ultrasound biomicroscopy is a highly informative method of its anatomic and topographic changes evaluation in cases with rhegmatogenous retinal detachment complicated by ciliochoroidal detachment and uveitis.